ANALISIS KONTEKS DALAM PENGEMBANGAN DAN IMPLEMENTASI KURIKULUM TINGKAT SATUAN PENDIDIKAN - Wildan, Wildan (Universitas Hamzanwadi, 2009)
The development and implementation of KTSP is basically under the coordination and supervition of education board. KTSP development must be based on the context (satndar isi) and output competence standard (Standar Komptensi lulusan) based and refers to curriculum development guide, and considering the school comite opinion. The first step in KTSP development and implementation is school analysing the situation and condition ( context analysis). This can be done through SWOT approach in the form of self evaluation about the school situation and condition. From the finding the real situation and condition of the school can be known, so that the intended program will reflect the effort to improve the internal school situation and condition based on opportunity analysis result and threat school extrrernal situation.